Laba Perusahaan Asuransi Umum di Bursa Efek Indonesia Dipengaruhi oleh Pendapatan Premi, Beban Klaim, dan Risk Based Capital - Puteri Maharani; Ossi Ferli (The Indonesia Capital Market Institute, 2020)
This research was conducted to examine the effect of Premium Income, Claims Expenses, Investments, Risk Based Capital (RBC) on company profits (ROA). Premium Income (PP), Claims Expenses (BK), Investments Result (HI), and Risk Based Capital (RBC) are used as independent variables estimated to have an impact on company profits (ROA) as the dependent variable. This research was conducted at general insurance companies listed on the Stock Exchange for the period 2012-2017. The data obtained is by accessing the Indonesia Stock Exchange website. The sample in this study was selected using the Purposive Sampling method so there are only 8 insurance companies listed on the Stock Exchange for the period 2012-2017 that can be used in this study. The analysis technique used in this study is multiple regression analysis. The results of this study show Premium Income (PP) has a positive effect on company profits (ROA), Claim Expenses (BK) has a negative effect on company profits (ROA), Investments (HI) has no effect on company profit (ROA), and Risk Based Capital (RBC) has a positive effect on company profit (ROA)